2011
DOI: 10.1111/j.1440-1843.2011.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

Cough reflex sensitivity and airway inflammation in patients with chronic cough due to non‐acid gastro‐oesophageal reflux

Abstract: Chronic cough due to non-acid reflux may be related to cough reflex hypersensitivity caused by neurogenic airway inflammation and mast cell activation, in which weakly acidic reflux is possibly a major factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 36 publications
2
71
0
Order By: Relevance
“…Cough reflex sensitivity to capsaicin is similarly increased in patients with both acid and non-acid reflux [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Cough reflex sensitivity to capsaicin is similarly increased in patients with both acid and non-acid reflux [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Sputum was induced and processed as described previously [19]. Briefly, the subjects continuously inhaled the 4% hypertonic saline solution through an ultrasonic nebulizer (YS9801, Yisheng Corp., Shanghai, China) and were asked to expectorate sputum into a sterile pot every 5 min, after blowing their noses and rinsing their mouths.…”
Section: Methodsmentioning
confidence: 99%
“…However, other biomarkers of inflammation such as prostaglandin D2 and histamine were not significantly increased in these samples [16]. Another study on inflammatory markers in 20 GER patients with cough or mild asthma found no elevation in fibrinogen levels in induced sputum, and an elevation in ECP was more associated with asthma than with GER.…”
Section: Biomarkers In Sputummentioning
confidence: 99%
“…In another study patients with GER and chronic cough were shown to have 50–100 times more of the tachykinin substance P in their sputum when compared to GER patients without chronic cough or healthy subjects [16]. Similarly, a cross-sectional study of 32 subjects showed a positive association between GER and the tachykinins substance P and neurokinin A in induced sputum samples, both in asthmatics and nonasthmatics.…”
Section: Biomarkers In Sputummentioning
confidence: 99%
See 1 more Smart Citation